Factors that influence the use of digital payments as ease of transactions in the digital era - Nurdin, Alya Aulia; Pamungkas, Agus Bayu; Kholifah, Alfina Nur (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2023)
Many things in the line of life are already shifting towards digital. The use of financial technology in the digital era is one of the new choices that are in great demand as a tool for transactions in society. The use of fintech payment services can further maximize banking product services so that the payment system in buying and selling transactions becomes more effective and efficient. This study aims to find out how massive the use of financial technology services is in digital payment transactions in the community and find out what factors influence people to use digital payment services so that they can facilitate their activities in transactions in their daily lives. The method used in this study is quantitative in the form of a survey. The questionnaire survey was distributed via Google Form to 102 respondents from the age range of 14-30 years. After that, the data was analyzed using the partial least square–structural equation model (PLS-SEM). The results showed that the proposed model is moderately accurate with an R-square value of 0.561. In this study, effort expectancy and performance expectancy significantly influence the intention to use digital payment. Meanwhile, culture, perceived security, and social factors did not have a significant influence. The conclusion is that the intention to use digital payment will get stronger if the service related to performance expectancy and effort expectancy are simultaneously improved.